STUDIES ON FECUNDIT-Y OF PUNTIUS SARANA (HAM.) IN RELATION TO TOTAL LENGTH, TOTAL WEIGHT AND OVARY WEIGHT - Kumar, Santosh; Somdutt, Somdutt (Journal of Indian Fisheries Association, 2015)
A total of forty three mature female of Puntius sarana (Ham.) ranging from 204 mm to 320 mm in length and 102 to 482 gin weight were used for present studies. The relationship between fecundity with respect to toal length (TL), total weight (TW) and ovary weight (OW) was found to be linear. The coefficient of co-relation ir’ of the above relationships was found to be 0.5947, 0.5761 and 0.9837 respectively. All these values are highly significant (P=O.Ol) indicating a close relationship between these parameters. However, as indicated by value of ’r’ (0.9837), the fecundity is more closely related to ovary weight and hence the ovary weight may be a better index of fecundity than the total length or weight. Keywords: Punitius sarana. fecundity, total length, total weight and ovary weight